MISI BUDAYA MIGRAN UNSKILL JAWA DI KOTA DENPASAR - Mariyah, Emiliana; Fredyarin, Novena Ade (PIRAMIDA; Vol 10 No 2 (2014): Jurnal PIRAMIDA, 2014)
Reproduction of culture can influence adaptation strategies and identity building. In this process there is domination and subordination of culture, and in the social order it can be observed the process of resistance to maintain identity, as an ethnicity. On the one hand, the process of cultural reproduction involves how the culture of origin are represented in this new environment, on the other hand, the identity of the origin of which has become part of a person’s life history can not be abandoned, even the culture of origin tends to be a guide in life in a new place (cultural mission). The principle mission of Javanese culture: ‘building castles /omah’ in the place of origin, while making slums in the areas of migration. Due to the simple life of Javanese (the unskilled migrants) in Denpasar consequently it creates slums, so that Denpasar as tourism area is hegemonized by 35 locations of slums. On the basis of these reasons, the paper analyzed 1) What are the unskilled Javanese migrants’ adaptation strategies?; 2) What are the implications of the unskilled Javanese migrants’ cultural mission? The process of data collection was conducted by using field observations, in-depth interviews with 15 informants from migrants, as well as focus group discussions and studies examining documents with reading and browsing the internet. In dissecting the Javanese unskilled migrants’ adaptation problems in Denpasar, it was used the theories of Maslow’s needs hierarchy theory and cultural configurations. The results showed that, first, to live a life in a new place (the city of Denpasar), the unskilled Javanese migrants are able to adapt socially with the local population (the Balinese people) in harmony and to carry out their cultural mission, which still retains their cultural traditions. Second, the mission of the cultural mission of the unskilled Javanese migrants in Denpasar have implications (impacts), namely the strengthening of ethnic identity of Java, shifting consumption patterns and lifestyles as well as their commitment to sustaining their own culture. It is suggested that tolerance and harmonious cooperation PIRAMIDA Vol. X No. 2 : 94 - 99 ISSN : 1907-3275 Volume X No. 2 Desember 2014 95 Emiliana Mariyah dan Novena Ade Fredyarin between migrants and natives (the Balinese people) that has existed in the slums communities in Denpasar need to be maintained to establish the life of a multicultural society.
Keywords: cultural mission,the unskilled Javanese migrants, the City of Denpasar.